Desenvolvimento de sistema para leitura de código de barras com “feedback” para aquisição e segurança de produtos em supermercados - Simões, Eduardo Dusanoski (2015)
Supply chain is one of the sectors where there is more competition among companies, these companies find themselves forced to be more efficient. This paper presents the development of an automated system to reduce costs and increase agility for consumers when making their purchases, by making the use of these establishments more attractive. Several systems that allow consumers to be the cashier himself already exist in other countries and are already being used. However most of them have not a system that protects the retailer from thieves, making these systems unattractive. This project aims to develop a device that uses barcode technology and security system to enable consumers to just pay for their goods instead of waiting for a cashier to check them out. The aim is to, before the end of the purchase, make the consumer already have information of the value to be paid and then only need to do the payment without having to wait for a confirmation. At the same time, the property is protected against fraud by malicious costumers. It begins by presenting the technologies that are being utilized such as bar code systems and security systems for libraries. After that, the integration of systems and the development of the automated system for purchases at supermarkets are shown. Finally the obtained results and an evaluation about the implementation viability.